Calibration and Precise Detection of the Irregular Drift of the Tidal Zero Point for a short/medium term Tide Station - Huang, C.; Lu, X.; Sun, W.; Huang, X.; Deng, K.; Zhao (China)., X. (The International Hydrographic Review, 2018)
The tide gauge is one of the most important auxiliary sensors in hydrographic surveying. Medium and short-term tide stations are established using pressure-type tide gauges to achieve the water level control for the depth measurement along the coast. Affected by the complex marine environment, one of the main factors in determining the accuracy of the water depth measurement is the irregular drift of the tidal zero point, which is usually deter-mined during the engineering practice. However, the relevant theoretical research on detection and correction lags. In this paper, the occurence of irregular drift about tidal zero is analyzed, and a mathematical model for precise processing of drift detection and correc-tion is proposed. Based on the processing of nearly one month of simultaneous tide data at the long-term Dinghai station, the temporary station at Gangxin, as well as the long-term Dafeng station and temporary Sanyazi station, the effect of two daily average sea surface calculation methods on different constituents are analyzed. The results show that the new proposed model is suitable for the precise processing of irregular drift of tide zero point. After the tide zero point correction, the accuracy of the water level observation data of the short-term Gangxin and Sanyazi tide stations is improved from decimetre (dm) to centime-tre (cm) levels.